Research on Roll Variable Speed Grinding Based on Adaptive Fuzzy Control - Bi Junxi; Gao Qing; Wang Shuwei (Institute of Advanced Engineering and Science, 2015)
The traditional method of improving the machining precision is mainly on account of changes in the workpiece and the grinding wheel in grinding process, including, considered the weakest of the workpiece from the axial stiffness, using center frame to increase the stiffness of the workpiece, take error compensation, and analyze the mechanism of gear grinding and the suppression measures of variable speed grinding and grinding chatter. Based on the analysis of the relationship among gear grinding mechanism, variable speed grinding and grinding chatter suppression and grinding precision, the variable speed micro-feed grinding process strategy based on adaptive fuzzy control is put up, that is according to the roller material and structure to reasonably determine the characteristics of grinding wheel and the parameters of grinding process. And with full consideration of roll grinders, changes of roller system along the axial stiffness and the deformation control in the roll grinding process, a new strategy of variable speed grinding micro-feed adaptive control optimization based on adaptive fuzzy control is proposed, which for improving the accuracy of the grinding roll presents a new and effective solution.